Preterm Birth Is Associated With Immune Dysregulation Which Persists in Infants Exposed to Histologic Chorioamnionitis - Sullivan, Gemma; Galdi, Paola; Borbye-Lorenzen, Nis; Stoye, David Q.; Lamb, Gillian J.; Evans, Margaret J.; Skogstrand, Kristin; Chandran, Siddharthan; Boardman, James P. (Frontiers in Immunology, 2021)
Introduction. Preterm infants are at increased risk of exposure to histologic chorioamnionitis (HCA) when compared to term-born controls, and this is associated with several neonatal morbidities involving brain, lungs and gut. Preterm infants could benefit from immunomodulatory therapies in the perinatal period, but development of rational treatment strategies requires improved characterization of the perinatal response to HCA. We had two objectives: the first, to characterize the umbilical cord blood immune profile in preterm infants compared to term-born controls; the second, to investigate the postnatal immune response in preterm infants exposed to HCA versus those who were not. Population. For objective one 59 term infants (mean gestational age (GA) 39+4 [37+3 to 42+0]) and 55 preterm infants (mean GA 29+0 [23+3 to 32+0]) with umbilical cord samples available were included; for objective two we studied 96 preterm infants (mean GA 29+1 [23+2 to 32+0]) for whom placental histology and postnatal blood samples were available. Methods. Placental histopathology was used to identify reaction patterns indicative of HCA, and a customized immunoassay of 24 inflammatory markers and trophic proteins selected to reflect the perinatal immune response was performed on umbilical cord blood in term and preterm participants and postnatal day 5 blood in the preterm group. Results. The umbilical cord blood immune profile classified gestational age category with 86% accuracy (95% CI 0.78-0.92), p-value=1.242x10-14. Pro-inflammatory proteins IL-6, MCP-1 and CRP were elevated in the cord blood of preterm infants whilst BDNF, C3, C9, IL-18, MMP-9 and RANTES were decreased, compared to infants born at term. In preterm infants, exposure to HCA was associated with elevations in 8 immune proteins on postnatal day 5 (BDNF, C3, C5a, C9, IL-8, MCP-1, MIP-1β and MMP-9) when compared to preterm infants who were not exposed. Conclusion. Preterm birth is associated with a distinct immune profile in umbilical cord blood and preterm infants exposed to HCA with evidence of a fetal inflammatory response have specific alterations in immune function that are apparent on day 5 of postnatal life.